Perancangan Sistem Evaluasi Kinerja Karyawan di PT Paramount Bed Indonesia - Elmor Benedict Wagiu; Adam Adam (TeIKa, 2018)
Employee Performance Evaluation is a very important thing in business activities. The difference in principlebetween superiors and subordinates makes business activities sometimes run not as desired. It needs anemployee performance evaluation activity that is useful for eliminating dissent, taking employeeperformance data, and seeing the development of the company with workers who have been employed.Therefore, the author wants to build a web-based program to make employees evaluation becomes easierand faster. And so writer tries to make a research, and the title of this research is “Designing an EmployeePerformance Evaluation System at PT Paramount Bed Indonesia”. With the existence of this web-basedprogram, it is expected that the use of technology will become more optimal, especially in the field ofemployee performance evaluation. The objectives of this study are: 1) Facilitating employee performanceevaluation activities. 2) Give a more accurate assessment, because all of the data taken will go directly intothe database. 3) Minimizing costs that have been used so far, such as paper, ink, etc. 4) To create easierdata monitoring that has been submitted by the user through the admin page. 5) Easy to determine thebest employees through the administrator page. The research method used in writing is the WaterfallModel. This employee evaluation system is expected to help PT Paramount Bed Indonesia to evaluateemployees without using paper and ink. The department head is also expected to be able to fill outevaluations through Smartphones, PCs and Notebooks. This evaluation system is also expected to assistthe General Affairs Department in managing evaluation data more accurately.Key Words: Information Systems, Evaluation.